Dificuldades de alfabetização enfrentadas pelos alunos das turmas 1°, 2° e 3° anos do ensino fundamental da escola Dom Ângelo Frosi, município de Abaetetuba – Pará - CORREA, Cristiney de Jesus Correa e (2023)
The aim of this study is to understand the difficulties of literacy faced by the students of the 1st, 2nd and 3rd years of elementary school at the Dom Ângelo Frosi School, addressing reflections about literacy and literacy as indispensable processes for children and also reflecting on the pedagogical doing in the school space. This study is the result of research carried out in a municipal public school, located in the Tucumanduba River, islands of the municipality of Abaetetuba-Pará. The school serves elementary and junior high school students, distributed in the morning, afternoon and evening shifts. The study is the result of a qualitative approach, being that bibliographical and field researches were carried out with participant observation and subject to critical reflections, approaching the theoretical reference with the analysis that allows to understand the relevant questions that involve the students learning. Participants in the research were teachers who work in minor elementary education, 1st, 2nd and 3rd years, students of these respective groups and parents of these respective students. The participants of this research contributed decisively to the development of this study and allowed to point out the main difficulties of the students in the process of literacy and literacy.